Incidence of Hip Fractures (Subtrochanteric and Intertrochanteric) in Sialkot in Last Five Years (Medical Forum Monthly, 2020)
Objective: To study the Incidence of hip fractures (subtrochanteric and intertrochanteric) in Sialkot last five years.Study Design: Retrospective StudyPlace and Duration of Study: This study was conducted at the Department of Surgery, Idris Teaching Hospital, Sialkot Medical College, Sialkot from January 2015 to 31st July 2019.Materials and Methods: A total of 121 patients were included in this study. There were 52(43%) patients were male and 69(57%) patients were female. The performa was designed to note down the demographic data and complications of hip fracture and lab test.Written Informed consent was taken from every patient included in this study. The permission of ethical committee was also taken before collection of data and publishing in the medical journal.. Participants were selected through non probability consecutive sampling technique.Results: At the age of 26-35 years, there were patients of hip fracture 9(17.30%) Male and 2(3%) female. At the age of 36-45 years the patients of hip fracture were 3(5.76%) Male and 5(7.24%) female. At the age of 46-55 years the patients of hip fracture were 3 (5.76%) Male and 4(6%) female. At the age of 56-65 years the patients of hip fracture were 6(11.52%) Male and 6(9%) female. At the age above 65 years the patients of hip fracture were 31(59.61%) Male and 52(75.36%) Female. There was cause of hip fracture due to fall or slippage was 31(59.61%) Male and 60(87%) female, due to RTA especially car accidents 19 (36.53%) Male and 06(9%) female. Due to obesity , there were 2(3.84%) Male and 3(4.5%) female were found. Conservative skin traction or bed rest there were 2(3.84%) Male and 4(6%) female were found. There were DHS 31(59.61%) male and 48 (69.56%) female , DCS 12(23.04%) Male and 14(20.28%) Female, due to I/M or I/L nail there were 7(13.46%) Male and 03(4.5%) female. There was complication of Blood clot leading to pulmonary Embolism 00(00%) Male and 1(1.5%) female.There was complication of Pneumonia 00(00%) Male and 2(3%) Female. There was complication of Infection 03(5.76%)Male and 04(06%) Female. There was complication of Cut out implant 01(1.92%) Male and 03(4.5%) Female. There was complication of Bed sores 00(00%) Male and 01(1.5%) Female. There was complication of Mortality in 1st year 03(5.76%) Male and 06(9%) Female. There was outcome and end result in hip fracture union of hip fracture was 43(87.75%) male and 54(85.71%) female, there was delayed union of hip fracture 02(4.1%) male and 03(4.76%) female, there was non union of hip fracture in 04(8.2%) Male and 06(9.5%) Female.Conclusion: It was concluded that there was hip fracture due to fall or slippage, car accidents and obesity.